Physiology, genomics, and biotechnological applications of extremophiles - Gunjal, Aparna B., 1981-; Thombre, Rebecca S., 1980-; Parray, Javid Ahmad (Advances in environmental engineering and green technologies (AEEGT) book series., 2022)
"The focus of this book is on the advancement in mechanisms of the extremophiles which makes them able to survive under extreme conditions, taking the ecology of the extremophiles into consideration"--